1988
DOI: 10.1111/j.1365-2044.1988.tb09064.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on cardiovascular dynamics and coronary blood flow in geriatric patients

Abstract: The cardiovascular and myocardial effects of propofol and etomidate were studied in 20 geriatric patients (age 65-84 years) who underwent major upper abdominal surgery. Ten patients received propofol 1.5 mg/kg for induction of anaesthesia followed by a continuous infusion of 0.1 mg/kg/minute for maintenance; 10 patients received etomidate 18 mg for induction followed by 2.4 mg/minute for maintenance. Vecuronium was used for neuromuscular blockade. Cardiovascular dynamics were recorded in the awake state one mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(51 citation statements)
references
References 8 publications
4
40
1
6
Order By: Relevance
“…The previous studies have reported that fall in the arterial blood pressure by 25-40% following propofol induction. 7 Our results are comparable with the results obtained by the study of Kaur S 8 et al in their study SBP and DBP decreased in both the groups immediately after induction. But fall in SBP and DBP were significantly more in propofol group compared to etomidate group.…”
Section: Changes In Blood Pressuresupporting
confidence: 83%
“…The previous studies have reported that fall in the arterial blood pressure by 25-40% following propofol induction. 7 Our results are comparable with the results obtained by the study of Kaur S 8 et al in their study SBP and DBP decreased in both the groups immediately after induction. But fall in SBP and DBP were significantly more in propofol group compared to etomidate group.…”
Section: Changes In Blood Pressuresupporting
confidence: 83%
“…22 In addition, etomidate has no effect on arterial pressure and systemic vascular resistance, 2 and does not alter systemic vascular resistance in elderly patients undergoing upper abdominal surgery. 23 In this in vitro study, etomidate (5 × 10 -6 M) at a clinically relevant concentration had no significant effect on both phenylephrine-induced and KCl-induced contraction, whereas high dose etomidate (5 × 10 -5 M) attenuated the contraction. Any clinical implication for etomidate on the regional hemodynamics must be tempered by the fact that a large conduit artery like the aorta was used in this in vitro study, whereas organ blood flow is controlled by diameter changes of the arterioles that have diameters less than 150 µm.…”
Section: Clinical Applicationsmentioning
confidence: 65%
“…Propofol use causes dose dependent and speed of injection dependent effects. At the start of anaesthesia, induction leads to apnoea in more than one in four cases, the incidence of which increases if opioids are added [22]; infusion of propofol results in decreases in tidal volume and respiratory frequency [23]; systolic blood pressure decreases [24] and is associated with a cardiac depressant effect and a decrease in systemic vascular resistance [25]. Propofol may also cause upper airway collapsibility and obstruction, especially when patients transition from conscious to unconscious [26].…”
Section: Propofol and Opioidsmentioning
confidence: 99%